Application of Pancasila Values in Improving Students' Character and Learning Motivation in Elementary Schools - Damanik, Tia Amanda (International Journal of Students Education, 2024)
This study aims first to determine the role of the Implementation of Pancasila values in improving the character and learning motivation of students in elementary schools. The research method used in the article uses a qualitative approach that is descriptive or often referred to as a literature review, the author traces published articles related to the title or topic of research that the researcher has determined, the articles traced are limited to 10 articles and then the researcher filters them into 5 articles that are considered appropriate and close to answer this research. The results of the study showed that as many as 5 articles from the search results can be seen that the Implementation of Pancasila values helps increase student learning motivation, creates a positive learning environment, and fosters an attitude of mutual cooperation and mutual respect. The findings in this study are still not many articles that write that the Implementation of Pancasila values in improving the character and learning motivation of students in elementary schools. So the researcher provides recommendations for the need for support from the government, educational institutions, student environments, and parents to work together to improve students' abilities in fostering Pancasila values in forming student character and learning motivation